Katekese Ekologis Kontekstual Berbasis Simbol Batang Garing dalam Budaya Dayak - Kristeno, Marianus Rago; Chiaralazzo, Monica Innanda; Pius X, Intansakti (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
The ecological crisis calls for faith formation that can foster contextual ecological awareness among the faithful. One relevant approach is through catechesis that integrates local wisdom, such as the Batang Garing symbol in Dayak culture. This study aims to explore the ecological values embedded in the Batang Garing symbol and to reflect on them in the light of Church teachings in order to formulate a contextual ecological catechesis model. The method used is qualitative research with a literature study approach, employing descriptive-analytical and comparative analysis of theological and cultural sources. The findings show that Batang Garing contains values of relationality, cosmic balance, and moral responsibility that are aligned with the concept of integral ecology in Church teachings. The integration of these values into catechesis enables a more contextual, communicative, and transformative faith formation. The implication of this study highlights the importance of developing catechetical models based on local culture as an effective means to foster ecological awareness among the faithful and to encourage concrete actions in caring for creation as an expression of faith.